Assessing the effectiveness of a three-stage on-farm biobed in treating pesticide contaminated wastewater. (1st October 2016) - Cooper, Richard J.; Fitt, Peter; Hiscock, Kevin M.; Lovett, Andrew A.; Gumm, Lee; Dugdale, Steve J.; Rambohul, Justin; Williamson, Antony; Noble, Lister; Beamish, James; Hovesen, Poul
Abstract: Agricultural point source pesticide pollution arising from contaminated machinery washings and accidental spillages pose a significant threat to river water and groundwater quality. In this study, we assess the effectiveness of a three-stage on-farm biobed for treating pesticide contaminated wastewater from a large (20 km 2 ) commercial arable estate. The facility consisted of an enclosed machinery wash-down unit (stage 1), a 49 m 2 lined compost-straw-topsoil biobed (stage 2), and a 200 m 2 drainage field with a trickle irrigation system (stage 3). Pesticide concentrations were analysed in water samples collected fortnightly between November 2013 and November 2015 from the biobed input and output sumps and from 20 porous pots buried at 45 cm and 90 cm depth within the drainage field. The results revealed that the biobed removed 68–98% of individual pesticides within the contaminated washings, with mean total pesticide concentrations reducing by 91.6% between the biobed input and output sumps. Drainage field irrigation removed a further 68–99% of individual pesticides, with total mean pesticide concentrations reducing by 98.4% and 97.2% in the 45 cm and 90 cm depth porous pots, respectively. The average total pesticide concentration at 45 cm depth in the drainage field (57 μg L −1 ) was 760 times lower than the mean concentration recorded in the input sump (43, 334 μg L −1 ). There was no evidence of seasonality in the efficiency of biobed pesticide removal, nor was there evidence of a decline in removal efficiency over the two-year monitoring period. However, higher mean total pesticide concentrations at 90 cm (102 μg L −1 ) relative to 45 cm (57 μg L −1 ) depth indicated an accumulation of pesticide residues deeper within the soil profile. Overall, the results presented here demonstrate that a three-stage biobed can successfully reduce pesticide pollution risk from contaminated machinery washings on a commercial farm. Graphical abstract: Highlights: Contaminated machinery washings were contained in an enclosed wash-down facility. A lined compost-straw-topsoil biobed removed 68–98% of individual pesticides. Drainage field irrigation removed a further 68–99% of residual pesticide. Mean total pesticide concentrations were 57 μg L −1 after drainage field irrigation. Evidence of pesticide accumulation at depth within the drainage field.